2020
DOI: 10.1002/anie.202010436
|View full text |Cite
|
Sign up to set email alerts
|

Pentacyclic Nano‐Trefoil

Abstract: Tetra‐armed cyclen (1) bearing two 4‐(4′‐pyridyl)benzyl and two 3,5‐difluorobenzyl groups and its Ag+ complexes were prepared and structurally characterized. The complexes formed between 1 and Ag+ undergoes a reversible structural transformation between a 2:2 dimeric complex and a 3:5 pentacyclic trefoil complex with changes in the Ag+/1 molar ratio. It was also revealed that the 3:5 trefoil complex could encapsulate benzene and [D6]benzene selectively in solid‐state. The benzene‐included structures are stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…The ligand ( L a and L b ) and AgOTf solutions were prepared with concentrations of 8.3 × 10 –3 and 5.0 × 10 –1 M, respectively. The proton signals at the 2- and 6-positions of the aromatic side arms (H a , H b , and H c protons) of L a should shift to higher field if these aromatic side arms cover the Ag + inclusion in the cyclen. As shown in Figure , the H a , H b , and H c protons shifted to a higher field with the addition of Ag + , and the chemical shift changes stopped when 2 equiv of Ag + was added (H a , −0.85 ppm; H b , −0.12 ppm; H c , −0.45 ppm). The result shows that the aromatic rings cover the Ag + ions incorporated in the cyclen rings in the presence of 2 equiv of Ag + .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ligand ( L a and L b ) and AgOTf solutions were prepared with concentrations of 8.3 × 10 –3 and 5.0 × 10 –1 M, respectively. The proton signals at the 2- and 6-positions of the aromatic side arms (H a , H b , and H c protons) of L a should shift to higher field if these aromatic side arms cover the Ag + inclusion in the cyclen. As shown in Figure , the H a , H b , and H c protons shifted to a higher field with the addition of Ag + , and the chemical shift changes stopped when 2 equiv of Ag + was added (H a , −0.85 ppm; H b , −0.12 ppm; H c , −0.45 ppm). The result shows that the aromatic rings cover the Ag + ions incorporated in the cyclen rings in the presence of 2 equiv of Ag + .…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported “argentivorous molecules”, in which the aromatic side arms cover silver­(I) bound in the cyclen moiety by weak coordination. In the argentivorous molecules, when silver ions are trapped in the cyclen moiety, the aromatic side chains move as if they were trapping insects by Ag + –π interactions with the aromatic rings of the side chains and CH−π interactions between the side arms. There are two conformations of the aromatic side arms in silver­(I) complexes with argentivorous molecules. As shown in Figure , the silver complex with an argentivorous molecule having benzyl side arms exists as a racemic mixture of Δ and Λ forms in solution and the solid state. More recently, we reported that introducing chirality into the cyclen ring or one of the methylenes of the side chain gave one isomer with the conformation of the side arms controlled in one direction according to the stereochemistry of the chiral carbon. , In particular, when chirality is introduced into the cyclen ring, the cyclen can form complexes with Ag + on both the front and back sides …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, our group is interested in tetra-armed cyclens and their silver­(I) complexes, incorporating tetra-armed aromatic side chains, giving wide structural diversity in the resulting argentivorous molecules by Ag + –π and CH−π interactions. For example, we demonstrated that double- and tetra-armed cyclens bearing an anthracene or pyrene unit as side arms behave like an insectivorous plant (Venus flytrap) by Ag + –π interactions. More recently, we reported that an Ag + complex with tetra-armed cyclens with styrylmethyl groups incorporates chiral alkyl nitriles to afford a drastic enhancement of the molar ellipticity in CD spectra …”
Section: Introductionmentioning
confidence: 99%
“…As bipyridine-based ligands can form a variety of complexes with Ag + , e.g., those with 1G :Ag + molar ratios of 1:1, 2:1, and 3:2, we first observed changes in the nuclear magnetic resonance (NMR) signals of aromatic protons upon the addition of Ag + (0–3.0 equiv) to find the optimal conditions for 3:2 and 1:1 complex formation (Figure S1). The signal of H 1,2 shifted upfield until the addition of 0.7 equiv of Ag + , with no large changes were observed at 0.7–1.2 equiv of Ag + , which indicated that the 3:2 1G :Ag + complex was the thermo­dynamic product in the presence of 0.7–1.2 equiv of Ag + .…”
Section: Resultsmentioning
confidence: 99%
“…Ligand 1R , which lacks a glycine moiety, was also prepared as a reference ligand (Scheme S2). The Ag + ion was chosen as a guest ion since it allows the formation of a variety of coordination geometries, such as linear, triangular, square planar, and tetrahedral structures with different coordination numbers. Indeed, Ag–Ag interactions not only induce helical structures in complexes but also act as additional driving forces for the formation of metallo-supra­molecular nano­structures. Thus, we herein report a dynamic morphological transformation from a 1D needle-like structure to a 1D helical tubular structure with P -helicity via a 2D ribbon of the 1G ligand in the presence of 1.0 equiv of AgNO 3 in an aqueous solution to represent the first example of a dynamic morphology transformation in metallo-supra­molecular nano­structures.…”
Section: Introductionmentioning
confidence: 99%